2005
DOI: 10.1007/s00248-004-0148-x
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with the Plant-Growth-Promoting Rhizobacterium Azospirillum brasilense Causes Little Disturbance in the Rhizosphere and Rhizoplane of Maize (Zea mays)

Abstract: Inoculation with Azospirillum brasilense exerts beneficial effects on plant growth and crop yields. In this study, a comparative analysis of maize (Zea mays) root inoculated or not inoculated with A. brasilense strains was performed in two soils. Colonization dynamics of the rhizobacteria were tracked in various root compartments using 16S rRNA-targeted probes and 4',6'diamidino-2-phenylindole staining, and the structure of bacterial populations in the same samples was analyzed by denaturing gradient gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 47 publications
3
51
0
1
Order By: Relevance
“…Members of this bacterial group are capable of degrading complex macromolecules, thus contributing to the turnover of carbon, nitrogen and phosphorus [24]. The analysis of a clone library of the maize rhizobacterial community indicated that Alpha-and Betaproteobacteria were dominant populations [25]. To the best of our knowledge this is the first detailed study to explore the feasibility of identifying maize rhizosphere bacteria using cultureindependent method and especially to obtain a better understanding of bacterial community structure and diversity using the method of sequencing of 16S rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this bacterial group are capable of degrading complex macromolecules, thus contributing to the turnover of carbon, nitrogen and phosphorus [24]. The analysis of a clone library of the maize rhizobacterial community indicated that Alpha-and Betaproteobacteria were dominant populations [25]. To the best of our knowledge this is the first detailed study to explore the feasibility of identifying maize rhizosphere bacteria using cultureindependent method and especially to obtain a better understanding of bacterial community structure and diversity using the method of sequencing of 16S rRNA genes.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation with these two rhizosphere microorganisms contributes to the emergence, development and grain production of crops such as wheat (Table 4), rice (Table 5), and maize (Table 6) (Baldani et al, 2008;Garcia de Salamone et al, 2010;Naiman et al, 2009). There is some evidence in controlled conditions for some crops that the application of certain PGPR does not change the structure of microbial communities (Herschkovitz et al, 2005). It was observed that there are some indications of the effect of PGPR inoculation have certain effects on the ShannonWeaver diversity index of the microbial communities associated to the rhizosphere of wheat (Table 7).…”
Section: Use Of Soil Microorganisms To Improve Plant Growth and Ecosymentioning
confidence: 99%
“…Previous studies have analyzed bacterial taxa associated with maize. Some of these studies have been focused on the culturable fraction [8][9][10] while others assessed bacterial diversity independently of culture [11][12][13][14]. However, none of these studies provided an analysis of rhizospheric and endophytic bacterial diversity assessed by both culture-dependent and culture-independent methods.…”
Section: Introductionmentioning
confidence: 99%